Hydrophobic and fire-resistant Polydimethylsiloxane/ZIF-8 hybrid coating on cotton textile for efficient oil-water separation - Sooriyanarayanan, Vikneswary; Wen, Ong Yi; Abdul Razak, Mus'ab; Mohd Tohir, Mohd Zahirasri; Choong, Thomas Shean Yaw; Abdul Hamid, Mohamad Rezi (Tamkang University, 2024)
The subject of oil-water separation has received tremendous attention in recent years due to an increasing amount of oily wastewater produced by industries and frequent incidents involving marine oil spills. Cotton fabrics can potentially be used as filtering element for oil-water separation but they are inherently flammable. Proper selection of surface finishing approaches/coating materials enable the fabrics to be endowed with improved fire safety and hydrophobic property for oil-water separation. In this work, a multifunctional coating comprises of polydimethylsiloxane (termed PMDS) and zeolitic imidazolate framework (ZIF-8) was applied to cotton fabrics via simple dip-coating method (termed COT-PDMS-ZIF8). COT-PDMS-ZIF8 displayed an improved hydrophobicity property with water contact angle of 140.3◦. The coated fabric preferentially allows oil to permeate through the fabric filter with permeate flux of 0.35 ml·m−2·min−1, resulting in oil-water separation efficiency ∼99%. Incorporation of crystalline ZIF-8 slows down rapid burning of cotton as evidenced by small derivative weight change (11.2% ·min−1 vs 16.21% ·min−1) from thermogravimetric analysis. Vertical flame test showed that the modified fabric burned longer than that of pristine fabric (38.75 sec vs 20.75 sec). Melt dripping behavior of cotton was successfully mitigated which further improve fire safety of the material. To sum up, a thin PDMS/ZIF-8 coating on cotton fabrics enhance hydrophobicity and fire performance of the fabrics considerably making them as promising candidate for oil-water separation. © The Author(’s).